Facile preparation of bithiazole-based material for inkjet printed light-emitting electrochemical cell. Issue 11 (20th February 2019) - Huo, Jingpei; Zou, Wanying; Zhang, Yubang; Chen, Weilan; Hu, Xiaohong; Deng, Qianjun; Chen, Dongchu
Abstract : Light-emitting electrochemical cell of bithiazole-based material was fabricated by solution processing rendered high external quantum efficiency over 12.8% and luminance of 1.8 10 4 cd m −2. Abstract : Light-emitting electrochemical cell of bithiazole-based material was fabricated by solution processing rendered high external quantum efficiency over 12.8% and luminance of 1.8 10 4 cd m −2 .